A Study on Formation of Hammer Transfer Stains in a Crime Scene - Bandyopadhyay, Samir; Basu, Nabanita (JOURNAL OF ADVANCES IN PHYSICS, 2014)
It is difficult to interpret hammer transfer strain in a crime scene. This paper lies in the argument that proper analysis of hammer transfer stains in crime scene may indicate the possibilities of proper incidence.